Problem of the Teachers Role in Pedeutology - Poškus, Kazys (Acta Paedagogica Vilnensia, 1996)
Present situation in education makes us review the teacher’s role, especially in the context of the ongoing educational reform. For the sake of objectivity it should be mentioned that not all the accusations of the authors of the reform directed towards the teachers of the Soviet period are adequate. Even during the Soviet times teachers encouraged the independent thinking of pupils, were looking for rational ideas of democratic education. The article deals with the problem of professional traits of the teacher, reviews the outlooks of different philosophical trends towards the teachers profession. According to various sociological, psychological and philosophical theories, teachers’ role in society is viewed very differently. We should decide what role our teachers are expected to play in contemporary society and what methods of teacher training are most adequate in this sense.
Keywords: Pedeutology; teacher; teachers profession; teachers role; professional traits of the teacher.